Multilayer dielectric elastomer with reconfigurable electrodes for artificial muscle - Fu, Hongbo (2023)
High-performance multilayer dielectric elastomer actuators (DEAs) are well-positioned to overcome the insufficient output force and energy density as artificial muscles. However, due to the fabrication process, the multilayer DEAs with nonmodifiable structures often suffer from the limitation of short lifespans and scalable preparation. Herein, reusable multilayer DEAs with the detachable and reconfigurable structure are fabricated. This is achieved by realizing scalable compliant electrodes using the continuous spatial confining forced network assembly (CSNA) method and combining the vacuum lamination (VL) approach to have good attachability and detachability with the VHB dielectric elastomer. The flexible roller-based CSNA method is used to prepare the large area compliant electrodes composed of α, ω-dihydroxy polydimethylsiloxane and electrically conductive nanoparticles. The fabricated electrodes can continuously work over 10 000 cycles at 40% strained stretching and maintain smooth surfaces to construct multilayer DEAs. Moreover, owing to the detachable configuration of the DEAs, the electrodes can also be recovered and reused for building new actuators. The lower limb assistive device is demonstrated by detachable multilayer spring roll DEAs, achieving approximately 3.1 degrees of flexion and extension movement of knee models under a voltage of 7 kV. The detachable and reconfigurable multilayer DEAs shed new light on the applications of wearable assistive devices.